1992
DOI: 10.2149/tmh1973.20.135
|View full text |Cite
|
Sign up to set email alerts
|

A new blackfly species of Simulium (Gomphostilbia) from Java, Indonesia (Diptera: Simuliidae).

Abstract: Abstract:A new blackfly species, Simulium (Gomphostilbia) parahiyangum sp. nov. is described based on the female, male, pupal and larval specimens collected from Java. This new species is very distinctive among the Gomphostilbia species in possessing prominent dorsal protuberances on abdominal segments 1-5 and a deep postgenal cleft reaching the hypostomium in the larval stage. By the number of antennal segments (11 vs. 10) the male of this species is easily distinguished from that of S. (G.) varicorne Edwards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…By sharing the deep postgenal cleft and dorsal protuberances on the abdomen in the larval stage, this species is also similar to S. (G.) parahiyangum originally described from Java (Takaoka and Sigit, 1992) . However, S.…”
Section: Descriptionsupporting
confidence: 56%
See 1 more Smart Citation
“…By sharing the deep postgenal cleft and dorsal protuberances on the abdomen in the larval stage, this species is also similar to S. (G.) parahiyangum originally described from Java (Takaoka and Sigit, 1992) . However, S.…”
Section: Descriptionsupporting
confidence: 56%
“…This species is readily distinguished from most of other Gomphostilbia species in the pupa by the eight short, slender filaments per side, and antennal sheath with nine well marked ridges on the outer margin, each covered with several cone-shaped tubercles, and in the larva by the prominent dorsal protuberances on the abdominal segments 1-5, several dark stout spines on the abdominal segments 6-8, and the deep postgenal cleft reaching the posterior margin of the hypostomium (Takaoka and Sigit, 1992 pointed out several characters of the Thailand specimens differing from those of the specimens from the type locality.…”
Section: Remarksmentioning
confidence: 87%
“…1B) (Jitklang et al, 2008;Takaoka and Davies, 1995;Takaoka and Suzuki, 1984;Takaoka and Sigit, 1992). The color of the hair tuft of S. (G.) curtatum, which was not clearly noted in the original description (Jitklang et al, 2008), is confirmed by observing the unique paratype female specimen (preserved in alcohol) deposited at Department of Infectious Disease Control, Faculty of Medicine, Oita University.…”
Section: Remarksmentioning
confidence: 93%
“…were reexamined, and the result shows that the pupa is S. (G,)Parahiyangum Takaoka and Sigit, originally described from Java (Takaoka and Sigit, 1992) and later recorded from Sabah and Sarawak (Takaoka, 2001a(Takaoka, , 2008b (Fig. IE, F (Takaoka and Davies, 1995 (Takaoka and Sigit, 1992;Takaoka, 2003Takaoka, , 2008a (Fig.…”
mentioning
confidence: 98%
“…IE, F (Takaoka and Davies, 1995 (Takaoka and Sigit, 1992;Takaoka, 2003Takaoka, , 2008a (Fig. 2C) (Delfinado, 1971;Takaoka, 1983) in having the wide male style (Fig.…”
mentioning
confidence: 99%